Defence and criticism of algorithmic governance - Daniel Innerarity (Revista CIDOB d'Afers Internacionals)
The problem of the relationship between algorithmic governance and democracy represents at once continuity and a break with traditional forms of bureaucratic administration. To understand its compatibility with democratic values, it is necessary to examine the scope of the expectations it raises, basically related to bringing more objectivity to political decisions and adopting them with greater consideration for our subjectivity as citizens who are the targets of these decisions. The limits of these promises force us to conclude on the inevitability of human decision-making, of politics in any technological environment, including the one shaped by the new forms of algorithmic governance.